Peranan Usahatani Tembakau di Berbagai Agro Ekosistem terhadap Pendapatan Petani dan Kesempatan Kerja di Kabupaten Sampang, Jawa Timur - Lia Verona; Supriyadi Tiortosuprobo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2016)
Research on the role of tobacco farming various agro-ecosystems to the farmers’ income and employment opportunity was conducted in Sampang district, East Java regency of in 2009/2010 using the survey methods. Object of research was in the field of tobacco farming in one year, in order to know: (1) the level of farm income, (2) the contribution of tobacco farming to the farmers' income, and (3) the role of tobacco farming in the labor market. Location of the study in 12 villages of 6 districts of tobacco production centers. Farmer samples are tobacco farmers in the three agro-ecosystems (paddy fields, dry land, and mountainous/hills) planted tobacco. Of the three agro-ecosystems there were 5 dominant cropping system. Each type of cropping system was selected randomly 10 farmers sample, so overall 50 farmers were selected as the sample of respondent, i.e: 20 tobacco farmers (paddy field), 10 tobacco farmers (dry land) and 20 tobacco farmers (mountainous/hills). Data on farming components were analyzed using to descriptive analysis and analysis of farming enterprise. Research findings indicate, total farmers in paddy fields, dry land and mountainous/hills were 6,192,354.00 IDR, 7,162,827.00 IDR, and 5,508,954.00 IDR. The total income from tobacco farming were 4,978,437.00 IDR, 5,233,159.00 IDR and 3,460,058.00 IDR. Tobacco farming in each ecosystem contributed 80 %, 73 %, and 63 % of total farmer income and contributions to the employment opportunity reached 59 %, 67 %, and 76 %. The conditions of income levels and labor absorption is relatively high showing that tobacco farming has the advantage of comparatively on rice farming and a secondary crops in tobacco traditional land. These conditions encourage the existence of a sustainable development of tobacco farming. ABSTRAKPenelitian peranan usahatani tembakau di berbagai agro ekosistem terhadap pendapatan petani dan kesempatan kerja dilaksanakan di Kabupaten Sampang Jawa Timur musim tanam 2009/2010 menggunakan metode survei. Obyek penelitian adalah usahatani di lahan tembakau dalam satu siklus usahatani selama satu tahun. Tujuan penelitian untuk mengetahui: (1) tingkat pendapatan usahatani di berbagai agro ekosistem, (2) kontribusi usahatani tembakau terhadap pendapatan petani, dan (3) peranan usahatani tembakau terhadap penyerapan tenaga kerja. Lokasi penelitian di 12 desa dari 6 kecamatan sentra produksi tembakau. Petani contoh adalah petani tembakau di tiga agro ekosistem (sawah, tegal, dan gunung/perbukitan) yang menanam tembakau dengan sistem pergiliran tanaman. Dari ketiga agro ekosistem teridentifikasi ada 5 tipe pola tanam dominan. Dari 5 tipe pola tanam yang tersebut, masing-masing dipilih dan ditetapkan secara acak sederhana (sampling random sample) sebanyak 10 petani contoh, sehingga secara keseluruhan terpilih 50 petani contoh sebagai responden (20 petani tembakau sawah, 10 petani tembakau tegal, dan 20 petani tembakau gunung/perbukitan). Data komponen kegiatan usahatani dianalisis menggunakan metode analisis deskriptif dan analisis usahatani enterprise. Hasil penelitian menunjukkan, usahatani di lahan sawah, tegal dan gunung/perbukitan dalam satu siklus usahatani, masing-masing menghasilkan pendapatan Rp 6.192.354,00, Rp 7.162.827,00, dan Rp 5.508.954,00. Total pendapatan ini diperoleh dari usahatani tembakau sebesar Rp 4.978.437,00, Rp 5.233.159,00, dan Rp 3.460.058,00. Usahatani tembakau pada masing-masing agro ekosistem memberikan kontribusi pendapatan sebesar 80 %, 73 %, dan 63 % dan penyerapan tenaga kerja 59 %, 67 %, dan 76 %. Kontribusi pendapatan dan serapan tenaga kerja yang relatif tinggi menunjukkan bahwa usahatani tembakau memiliki keunggulan komparatif terhadap usahatani padi dan palawija di lahan tradisional tembakau. Kondisi ini mendorong eksistensi pengembangan usahatani tembakau secara berkelanjutan.